Criminalistics Contents of Forensic Handwriting Expertises (Case Study Canton Sarajevo 2002. - 2007.) (Kriminalističke teme, 2015)
The inspiration for the paper and the problem(s) that the paper addresses: Thematically and structurally, this work was inspired by the desire of the author to try to check the application of established procedures prescribed for this area of expertise in specific court cases, using scientific methods.The goals of the paper (scientific and/or social): The subject of this research is the treatment of experts and expert witnesses in criminal proceedings in the field of criminal investigation and forensic expertise handwriting, aim of the work could be defined as an attempt to determine whether the experts who are engaged in criminal forensic examination of handwriting in the Courts of the Sarajevo Canton adhere to generally accepted scientific methodological principles.Methodology/Design: Methods used in this research are: content analysis, methods of description, classification and specialization, comparative method, and statistical methods for processing empirical data.Research/the paper limitations: Limitations of this study, possibly, may result from the unavailability of the entire sample of cases in the courts of Sarajevo Canton.Results/findings: The Study was conducted on a sample of 95 criminal cases in which it was performed 106 expertises by six different court experts. In the analyzed sample, in 18,86% of the cases the experts gave opinions with some degree of probability. In the analyzed sample, 94,34% of the presented expert opinions in the expert reports were in accordance with the final court judgment.General conclusion: Within analyzed sample of processed cases, methodological omissions – errors were observed during the expertise procedure, i.e. the application of professional rules, in 6,6% of cases.Research/the paper justifiability: Justifiability of the paper is in the fact that the paper represents research results of real court cases which envisaged handwriting expertise in Sarajevo Canton for the period 2002. – 2007, and the results of this study observed expertise omissions – errors in the application of the professional rules and skills.